2012
DOI: 10.1039/c2an35097a
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical investigations into Tau protein phosphorylations

Abstract: Hyperphosphorylation of Tau, a protein that stabilizes microtubules, leads to the breakdown of the microtubular structure and ultimately to the formation of neurofibrillar tangles within neurons. Here, we report monitoring of Tau phosphorylations electrochemically, using Tau protein films chemically linked to gold surfaces and 5'-γ-ferrocenyl (Fc) adenosine triphosphate (Fc-ATP) as a co-substrate. Fc-phosphorylation reactions of Tau are explored using the three protein kinases, glycogen synthase kinase (GSK-3β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…1,2 However, in many applications, these sensors are exposed to complex biological media along with the analyte of interest. The accumulation of biological components such as proteins, lipids, and polysaccharides on the sensor surface is referred to as biofouling.…”
mentioning
confidence: 99%
“…1,2 However, in many applications, these sensors are exposed to complex biological media along with the analyte of interest. The accumulation of biological components such as proteins, lipids, and polysaccharides on the sensor surface is referred to as biofouling.…”
mentioning
confidence: 99%
“…Ferrocene (Fc) is a typical sandwich metallocene compound, which contains a couple of planar cyclopentadienyl anion ring with 6π electrons and 6d electrons on Fe (II) [20,21]. It's remarkable that the introduction of Fc molecule on GO not only can draw into further function [22], but also can significantly increase the dispersibility and specific surface area of GO [23]. As a well-known intermediate mediator in electrochemical field, Fc shows excellent electrochemical proper-ties, including fast electronetransfer rate, low oxidation potential and stability of two redox states [24,25], drawing extensive attention in functionalization GO due to its excellent electronic transmission ability [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies suggested that AD brain and traumatic brain injury exhibit similarities between accumulation of amyloid peptides mainly beta-amyloid (β-A) and tau protein (Tsitsopoulos and Marklund 2013). To monitor AD in real samples such as interstitial fluid (ISF) and cerebrospinal fluid (CSF), both tau protein and β-A have served as potential biomarkers (Kolarova et al 2012; Martić et al 2012a; Martić et al 2012b; Martic et al 2013; Rains et al 2013; Tsitsopoulos and Marklund 2013). To make presented review well-focused and comprehensive, we highlight exclusively β-A as a potential biomarker for AD detection using nano-enabling biosensors.…”
Section: Introduction: Alzheimer’s Diseases and Challengesmentioning
confidence: 99%